Photon-triggered self-powered all electronics with graphene-silicon hybrid device - Kumar, Mohit; Lim, Jaeseong; Kang, Hyunwoo; Kim, Sangwan; Seo, Hyungtak (Nano Energy, 2021)
Breaking the electron-hole occupancy symmetry in graphene is a powerful approach for engineering novel optoelectronic phenomena. Traditionally, this has been achieved by electrostatic gating. However, the realization of such phenomena by using photons, without any external power supply, has remained a challenge. In this study, we developed photon-triggered, self-biased, graphene-based diverse electronic circuits, including lateral p–n and n–p homojunctions, switches, transistors, and logic gates (NOT, OR, and AND), which were further supported by local probe measurements. Moreover, the proposed device operates in a wide spectral range (from ultraviolet-visible-near-infrared range) under the self-biased condition (0 V) with fast temporal processing (~12 μs) even at the nanoscale (<50 nm). As immediate applications, we demonstrated high-speed (~72 km/h), event-based neuromorphic sensing. This work offers unprecedented opportunities on a single platform in the fields of digital/analog electronics and optoelectronics with nanoscale control and provides a neuromorphic solution to the issues encountered in conventional digital cameras.
Keywords: External power supplies; Homo-junctions; Hybrid devices; Nanoscale control; Single platform; Temporal processing; Visible near-infrared; Wide spectral range; Logic gates; Neuromorphic; Photon-triggered; Self-powered; Switches; Transistors